Implementasi Composite Performance Index (CPI) Pada Sistem Pendukung Keputusan Pemilihan Mitra Pengiriman Barang - Rhaishudin Jafar Rumandan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
Shipping services and business operations today will always be connected. Through goods delivery services, it can help in sending the products sold to the hands of customers. Thus, the selection of goods delivery partners becomes a crucial matter. The selection of freight forwarding service partners is usually done by looking at the profiles of the freight forwarding service partners and what services are provided. This takes time, because the company has to learn one by one the services provided. This research aims to apply the Composite Performance Index (CPI) approach in building a Decision Support System (DSS) for the selection of goods delivery partners in order to produce the right alternatives and according to needs. The CPI method solves problems based on the combined index value so that the best alternative can be determined. Based on the case study, the highest score was obtained, namely the alternative PT. Angkut Teknologi Indonesia with a score of 127.5, followed by PT. Dunia Express Transindo with a score of 122.5, PT. Indah Logistik with a score of 120 and PT. Siba Surya with a value of 100. The calculation results obtained by the system and manual calculations show the same value, this means that the system built produces valid calculations. The system has also been tested through a black-box testing approach with the results that all functions on the system can run properly.